Numerical and experimental study of concrete I-beam subjected to bending test with cyclic load - Ribeiro,Paula de Oliveira (2020)
Abstract This paper provides guidelines for cyclic loading bending test simulation and modal analysis of a reinforced concrete I-beam. For this purpose, experimental and numerical cyclic bending test were performed. In the experimental study, the natural frequencies of the structure in the intact and damaged states were measured. The simulation of the cyclic bending test was done with Concrete Damaged Plasticity model (CDP), implemented in Abaqus finite element software. Based on the experimental results, different constitutive models for concrete were evaluated. In order to evaluate the dynamic behavior of the structure in the numerical model, the automatic calibration of the finite element model by Genetic Algorithm (GA) was used. With the calibrated numerical model, methodologies for estimating the overall damage of the structure based on its dynamic properties were proposed. The results confirm that the well-designed numerical model is able to efficiently represent the cyclic loading bending test. In addition, the proposed global damage estimates demonstrate the coherence between numerical and experimental models.